“Acumulación de cadmio en almendras de cacao (theobroma cacao l.) Bajo la influencia de plantaciones de banano en el cantón El Empalme”. - Valencia López, Naomy Eloísa (2022)
In the cocoa marketing chain, cadmium concentrations are becoming a problem due to the deterioration of the quality of the soil and the product, especially due to the permissible limits established by the European Union established in the country's legislation. This research determined the accumulation of cadmium in cocoa beans (Theobroma cacao L.) under the influence of banana plantations in the Empalme canton. The measurement presents itself out with mass spectrometry, establishing a survey to know the reality of the cocoa